1999
DOI: 10.1038/sj.ejcn.1600881
|View full text |Cite
|
Sign up to set email alerts
|

Varying the protein source in mixed meal modifies glucose, insulin and glucagon kinetics in healthy men, has weak effects on subjective satiety and fails to affect food intake

Abstract: Objective: To evaluate the in¯uence of three dietary protein types (casein, gelatin, soy protein) on satiety and food intake, at two levels of loading (total energy of test meals: 3.6 or 1.8 MJ). Design: The study employed a repeated measures design. Test meals were controlled for energy, macronutrients, ®ber and palatability, and contained about 23% energy as protein (of which about 65% was experimentally manipulated). Postprandial subjective satiety and hunger, plasma glucose, insulin and glucagon were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
2
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 23 publications
1
52
2
1
Order By: Relevance
“…A mixed meal study of Lang et al of healthy men ingesting casein, gelatin or soy protein resulted in no difference in the satiety effect. However, there were significant effects on the kinetics of metabolic response (Lang et al, 1999). Glucose and insulin responses following casein-enriched meal lagged 1-1.5 h behind responses following soy protein-enriched meal.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A mixed meal study of Lang et al of healthy men ingesting casein, gelatin or soy protein resulted in no difference in the satiety effect. However, there were significant effects on the kinetics of metabolic response (Lang et al, 1999). Glucose and insulin responses following casein-enriched meal lagged 1-1.5 h behind responses following soy protein-enriched meal.…”
Section: Discussionmentioning
confidence: 93%
“…In six healthy males, the postprandial plasma insulin level increased, with a higher insulin/glucagon ratio, when fed beef rather than a fish meal (Soucy and Le Blanc, 1999). In another group of healthy men, modification of the protein source in mixed meals containing either casein, gelatin or soy protein was associated with diverging kinetics of postprandial blood glucose (Lang et al, 1999).…”
Section: Introductionmentioning
confidence: 91%
“…However, the effect of the nature of the proteins was not present in all experiments. Indeed, various proteins have been used in other experiments described in the literature, and it is still not clear if the nature of the protein can significantly affect the feeding response studied (egg albumin, casein, soya or whey or pea proteins in human subjects) (30,31) . The results observed with biochemically very different proteins strongly suggest that the satiating effect of protein is primarily a very general property that does not depend on such specific characteristics of one or another protein (3) .…”
Section: Protein Snacks (Or Loads)mentioning
confidence: 99%
“…Lang et al (1998) found no differences between the effect of egg albumin, casein, gelatin, soy, pea, or wheat gluten on appetite. Subsequently, Lang et al (1999) found a weak effect on satiety but no difference in energy intake after consumption of casein, gelatin, or soy protein based meals. found no difference on appetite and energy intake of a whey or casein preload and found whey, soy, and gluten protein tended to reduce ad libitum food intake equally.…”
Section: Introductionmentioning
confidence: 99%